Potensi Jamur Endofit dari Daun Jambu Nasi-Nasi (Syzygium zeylanicum) sebagai Antibiotik Alami dalam Mengobati Jerawat - Syarifah, Syarifah; Yusfarani, Delia; Kharism, Sully P; Fauzan, Ahmad R (Universitas Andalas, 2024)
Endophytic fungi are microscopic organisms that live in leaves, stem bark and root bark at certain periods by forming colonies without harming their hosts, and even have a mutually beneficial relationship. Endophytic fungi generally produce secondary metabolites that have useful biological activities such as antibacterial, antioxidant, antiviral and anticancer. Endophytic fungi can be found in various types of plants, especially in medicinal plants, such as Syzygium zeylanicum, which is one of the many medicinal plants found in Indonesia. A total of 6 endophytic fungal isolates were successfully isolated from the nasi-nasi guava, namely Septonema, Lasiodiplodia pseudotheobromae, Trichoderma aureoviridae, Acremonium, Sclerotium, Scopulariopsis asperula. Antibacterial activity was carried out using the agar diffusion method. The percentage of antibacterial activity values shows that SL1, SL2, SL3, SL4, SL5 and SL 6 all have strong antibacterial activity against the bacteria Staphylococcus aureus and Propionibacterium acnes, while for the bacteria Staphylococcus epidermidis it is found that isolates SL1, SL4 and SL6 have strong antibacterial activity and isolates SL2, SL3 and SL5 had moderate antibacterial activity. This category shows that the extract of the endophytic fungus Syzygium zeyanicum has antibacterial potential.